Accurate in-operando study of molten carbonate fuel cell degradation processes -part I: Physiochemical processes individuation. (20th November 2018) - Santoni, F.; Della Pietra, M.; Pumiglia, D.; Boigues Muñoz, C.; McPhail, S.J.; Cigolotti, V.; Nam, S.W.; Kang, M.G.; Yoon, S.P.
Abstract: This work has the difficult task to deeply study the electrochemical processes that occur inside a 100 cm 2 of Molten Carbonate Fuel Cells (MCFC) impedance spectra using the high resolution of Distribution of Relaxation Time (DRT) method. Using this method, it is possible to shed light on the different physicochemical processes occurring within these cells, identifying the characteristic relaxation times by means of an appropriate experimental campaign where temperature and gas compositions in anode and cathode were varied one at a time. The quality of the recorded spectra was verified by Kramers-Kronig relation before applying DRT calculations. In this work, five distinct and separated peaks with different time constants ranging from 0.01 to 500 Hz were identified and associated with physiochemical processes of the cell. Three peaks at high frequency represent the charge transfer processes in anode and cathode active sites. The other two, located at low frequency, are associated with the gas diffusion in the electrodes and to the gas conversion process. This study represents the first application of the DRT approach to this technology allowing to understand the physicochemical origin of the individual polarization processes controlling the cell performance and the degradation. The analysis of degradation processes using the DRT method and the physiochemical processes identification presented in this paper will be shown in part II of this work. Highlights: The first application of DRT approach to MCFC impedance Spectra is presented. Five processes controlling the cell performance are individuated using DRT method. Repeatability and reproducibility of the DRT results in MCFCs are demonstrated. Three peaks with a high-frequency domain are related to Charge Transfer Processes. Two peaks with a low-frequency domain are associated with Mass Transfer Mechanisms.